2019
DOI: 10.1002/jez.2320
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine fish assemblages present a species‐specific difference in the multixenobiotics resistance activity

Abstract: We investigated the activity of the multixenobiotic resistance (MXR) phenotype, a biological defense system in aquatic organisms, in the fish assemblages of two tropical estuaries with different degrees of environmental impacts, the Paraiba River and Mamanguape River Estuaries. The aim of this work was to compare the activity of the MXR phenotype of different fishes to test the hypothesis that each species has an inherent activity level and to use this activity as a bioindicator of aquatic contamination. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…There is a correlation between the level of pollution identified and the expression of this glycoprotein; therefore, MXR can be considered a generalized biomarker of aquatic contamination [14]. In this study, the results showed that intense labeling in group 1 indicated a high concentration of pollutants in the environment.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There is a correlation between the level of pollution identified and the expression of this glycoprotein; therefore, MXR can be considered a generalized biomarker of aquatic contamination [14]. In this study, the results showed that intense labeling in group 1 indicated a high concentration of pollutants in the environment.…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, others processes related to cell protection and responses to multixenobiotics have been investigated with an emphasis on the expression of P-glycoprotein (P-gp) [11][12][13][14]. P-gp is a transmembrane carrier glycoprotein present in several aquatic organisms, also known as ABCB1.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors must be considered to determine the most appropriate experimental design for toxicity tests, including the chemical complexity of the toxicant, persistence in the environment, and the degree of lethality (Gonçalves, 2004). In addition, the response that a living organism presents when exposed to a toxicant may vary according to the species of the animal (Macêdo et al, 2019). Physiological parameters, such as age, size, and sex, as well as the physical‐chemical parameters of the water, including pH, oxygenation, and the composition of the pesticide, can also influence the results obtained in the toxicity tests, which causes variance in the evaluated traits, as seen in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…These economic activities together with the impact of urban wastewater, have been leading to an intense environmental degradation of the estuary. Recent studies have shown a higher degree of human disturbance in the Paraiba River estuary, such as a higher nutrient enrichment, microplastic pollution, and revealed a high activity of a cellular detoxification by fishes, which indicates a high concentration of pollutants in the water of the Paraiba River estuary (Alves et al 2016, de Moura et al 2016, Santos et al 2017, David et al 2018, Macêdo et al 2019.…”
Section: Study Areamentioning
confidence: 99%